IMPLEMENTATION OF E-SAMSAT SERVICE INNOVATIONS IN AN EFFORT TO INCREASE MOTOR VEHICLE TAXES AT THE SERANG CITY SAMSAT OFFICE - Asih Machfuzhoh; intan Puspanita; Karlina Eka Putri (Review of Accounting and Taxation, 2023)
Purpose - This writing is to determine the application of e-Samsat service innovation in increasing motor vehicle tax revenues as well as the supporting and inhibiting factors for the implementation of e-Samsat Design/methodology/approach - This writing uses a descriptive method with data collection techniques in the form of interview, observation and documentation techniques. The object of writing is the Serang City Samsat Office. Finding - The results of the study indicate that e-Samsat service innovation is one of the efforts to increase motor vehicle tax revenues. The supporting factors for the e-Samsat service make it easier for the public to pay motor vehicle taxes with online transactions, supporting infrastructure, and a fast and smooth network system, while the inhibiting factor found is that e-Samsat is not fully online. system, there is still a lack of e-Samsat socialization. Samsat to the community, and the habit of using formal and informal intermediary services which are still more popular with the community Originality - to achieve the goal of better e-Samsat innovation, the Serang City Samsat Service has perfected e-Samsat into a full online system, especially in the PKB payment procedure, intensified the socialization of e-Samsat to the public, and collaborated with more banks. Keyword - Implementation, e-Samsat, Motor Vehicle Tax. Paper Type – Research Paper